Pre-service teachers' predilection of writing strategies in ESL classrooms - Palpanadan, Dr. Sarala @ Thulasi (IPGK Temenggong Ibrahim, 2016)
This research is done with the hope to shed some light on the preferred strategies and approach of the pre-service teachers in adopting product approach (FDA) and process approach (PCA)as writing instructions in the selected ESL classrooms. The PDA emphases on the final piece of writing while PCA aims at the development of the writing process. The FDA which is popular in the contemporary ESL classrooms seems to be useful in some ways. Teachers are able to cover syllabus and topics on time and reach out to students by assessing students' writing. On the other hand, researchers argue that the strategies of PCA help students to get involved in the writing process and make students to become less fearful to start writing and thus, help to improve the students' writing. However, PCA is less popular currently due to its tediousness of preparation of several drafts that consumes ample of time. Hence, this study analyzes the features of both the approaches thoroughly. This research hopes to be an eye opener to all educators especially the pre-service teachers in terms of writing instructions to help their students learn the necessary writing skills more sufficiently in the future.